FENOMENOLOGI LARANGAN PERNIKAHAN ANTAR-SUKU DALAM PERSPEKTIF HUKUM ISLAM: STUDI KASUS MASYARAKAT BUTON DAN KEI - Asbarin; Amalia, Nabila Nailil (TAHKIM, 2024)
ABSTRAK This study aims to analyze public perceptions regarding the prohibition of inter-tribal marriage among the Buton and Kei tribes, using the perspective of maqasid al-sharia and 'urf through a phenomenological approach. This research is a descriptive qualitative research, where a phenomenological approach is used to understand people's subjective experiences related to the prohibition. The primary data in this study were obtained from direct interviews with the Buton and Kei tribal communities, while secondary data was obtained from relevant documents, such as Islamic legal literature and local customary studies. Data collection techniques include in-depth interviews, participatory observations, and documentation studies. The phenomenological data analysis technique used involves two main stages, namely Horizonalization and Cluster of Meaning. In the first stage, each participant's statement was analyzed in parallel without initial assumptions, then grouped in the second stage to find relevant meanings related to public perception. The results of the study show that from the perspective of maqasid al-shharia, this prohibition of inter-tribal marriage is considered as part of the efforts of hifdz al-nasab (safeguarding offspring), which includes the importance of maintaining genealogy and family honor. Public perceptions are divided into three main groups: those who agree with the ban, those who are moderate or neutral, and those who resist. In addition, from the point of view of 'urf, the prohibition is categorized as 'urf sahih (legitimate tradition), which is in line with the accepted principles of Islamic law. Keywords: Islamic law, marriage, ethnicity, phenomenology